2020
DOI: 10.1177/0013124519896861
|View full text |Cite
|
Sign up to set email alerts
|

Culturally Responsive Pedagogy and Mathematics Through Creative and Body-Based Learning: Urban Aboriginal Schooling

Abstract: Global neoliberal imperatives that numerically measure student success through standardized testing undermine the educational outcomes of students, in particular Indigenous students, and construct a seemingly fixed reality that avoids State responsibility to address structural inequality in Australia. Achievement gaps between Indigenous and non-Indigenous school students in mathematics have become an urgent international problem. Although evidence suggests that culturally responsive pedagogies (CRPs) improve s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…The authors suggested that probability lessons embedded in cultural context help students to build connections between content (probability) and cultural context and, as a result, students can broaden their perception of mathematics. This suggestion aligns with culturally responsive pedagogy (Averill et al, 2009;O'Keeffe et al, 2019;Rigney et al, 2020) that is being promoted in multicultural settings. The game Lu-Lu can be used with students at the high school level with adaptations.…”
Section: Discussionsupporting
confidence: 62%
“…The authors suggested that probability lessons embedded in cultural context help students to build connections between content (probability) and cultural context and, as a result, students can broaden their perception of mathematics. This suggestion aligns with culturally responsive pedagogy (Averill et al, 2009;O'Keeffe et al, 2019;Rigney et al, 2020) that is being promoted in multicultural settings. The game Lu-Lu can be used with students at the high school level with adaptations.…”
Section: Discussionsupporting
confidence: 62%
“…In a 2012 audit of pre-service teacher training Moreton-Robinson et al [ 68 ] found that ‘Unless the relationship between racial privilege and racial disadvantage is understood the development of an effective Indigenous pedagogy remains beyond the scope of the national standards’. However, culturally responsive pedagogies, for instance, provide frameworks towards curriculum that are derived from critical theory, centring social justice and the classroom as a tool for social change [ 69 , 70 , 71 , 72 , 73 ]. Similarly, Ramsden [ 74 ] discusses anti-racism in nursing education as a foundational concept for the application of cultural safety education.…”
Section: Discussionmentioning
confidence: 99%
“…Schooling provides a general disposition ("cultured habitus") towards STEM learning, for example, which may not resonate with individuals in the community. The gaps between children's local rural knowledge (Avery and Kassam, 2011) and school science can be bridged through place-conscious pedagogies which serve to legitimize local STEM-knowledges (Rioux et al, 2018;Rigney et al, 2020). If the concept of STEM learning offered by the school is not embraced by the community, students are likely to lack encouragement to take up or continue STEM study.…”
Section: Ways Of Knowing Being and Valuing Of Stem Knowledges And Practicesmentioning
confidence: 99%
“…Rigney's contribution to STEM has included a focus on digital inclusion (Rigney, 2014) in classrooms and more recently on mathematics within Culturally Responsive Pedagogies (Rigney et al, 2020), and more specifically applying Creative and Bodybased Learning (CBL). In their study Rigney et al found that for Aboriginal students engaged with CBL "there was a decrease in student dissonance in the classroom and a stronger community of learners" (p. 1168).…”
Section: Aboriginal Knowledges Standpoints and Stemmentioning
confidence: 99%
See 1 more Smart Citation